Aplikasi Pengenalan Tata Surya Menggunakan 3d Hologram Berbasis Android - Ardy Bagus Sugiharto (LPPM STIKI MALANG, 2020)
In the current system, students generally know the solar system only from books obtained from schools. The pictures in the book are only 2D so that students find it difficult to imagine the original shapes of the planets and solar systems. However, to get to know the solar system, it would be better to use a teaching aid as a supporting tool to complement existing learning media. With the 3D Hologram Technology, the writer wants to use it to introduce the solar system to 6th grade elementary school students using an android-based smartphone by applying 3D Hologram technology as an attractive learning medium in tune with the times, there are lots of educational applications but not from the younger generation who don't want to study the system. solar but it is a delivery method that must be packaged well following developments so that it attracts a lot of user interest to try which will then end up learning the contents of what is delivered in the application, so for that an application for recognition of the solar system using 3D Hologram Pyramid with added value speech recognition feature is made. included in this application, the shape of the object is not only an image but is in the form of 3 dimensions that can be seen 360Â° horizontally so that the planetary object looks more real, the advantage in this application is that the user does not need a lot of physical interaction between them. artphone and user because the speech recognition feature has been provided so that the user only needs to give commands via voice. It can be concluded that 3D Hologram technology can be used as a means of introduction not only for 6th grade elementary school students but also for Indonesian people.